Comparison of Gray Matter Atrophy in Behavioral Variant Frontal Temporal Dementia and Amyotrophic Lateral Sclerosis: A Coordinate-Based Meta-Analysis - Luo, Chunyan; Hu, Na; Xiao, Yuan; Zhang, Wenjing; Gong, Qiyong; Lui, Su (Frontiers in Aging Neuroscience, 2020)
Background: There is growing evidence supporting behavioral variant frontotemporal dementia (bvFTD) and amyotrophic lateral sclerosis (ALS) as extreme points of a disease spectrum. The aim of this study was to delineate the common and different patterns of gray matter atrophy associated with bvFTD and with ALS by pooling together the results of previous voxel-based morphometry (VBM) studies. Methods: We retrieved VBM studies that investigated gray matter atrophy in bvFTD patients vs. controls and in ALS patients vs. controls. Stereotactic data were extracted from those studies and subsequently tested for convergence and differences using activation likelihood estimation (ALE). A behavioral analysis using the BrainMap database was performed to assess the functional roles of the regions affected by bvFTD and/or ALS. Results: Our study demonstrated a convergence of gray matter atrophy in the frontolimbic structures that involve the bilateral anterior insula and anterior cingulate cortex. Comparing the pattern of GM atrophy in bvFTD and ALS patients revealed greater atrophy in the frontomedial cortex, bilateral caudate, left anterior insula, and right thalamus in those with bvFTD and a higher degree of atrophy in the right motor cortex of those with ALS. Behavioral analysis revealed that the pattern of the affected regions contributed to the dysfunction of emotional and cognitive processing in bvFTD patients and the dysfunction of motor execution in ALS patients. Conclusion: Our results revealed a shared neural basis between bvFTD and ALS subjects, as well as a specific and distinct neural signature that underpinned the clinical manifestations of those two diseases. Those findings outlined the role of the frontomedial-caudate circuit in the development of bvFTD-like deficits in ALS patients.